POTENSI ISOLAT ACTINOMYCETES SEBAGAI ANTIMIKROBA TERHADAP BAKTERI SALMONELLA TYPHI - Hilwah (2020)
Actinomycetes are aerobic bacteria. Actinomycetes are microorganisms that have an important role because their secondary metabolites are rich in benefits, such as antimicrobial, antitumor, and antiparasitic. This study aims to determine the antimicrobial potential of Actinomycetes isolates from Bogor Botanical Gardens against the growth of Salmonella typhi. The research design used an experimental design. Rejuvenation of Actinomycetes isolates using spread plate method on media Starch Casein Agar (SCA) with six serial dilutions of 10-1, 10-2, 10-3, 10-4, 10-5, and 10-6. The antimicrobial test used the liquid dilution method to determine the value of the minimum inhibitory concentration with Trypticase Soy Broth (TSB) media followed by colony calculations on Salmonella Shigella Agar (SSA) media to determine the value of the minimum kill concentration and the antimicrobial potential. Secondary metabolites Actinomycetes have antibacterial mechanisms are inhibiting bacterial cell wall synthesis, inhibiting bacterial protein synthesis, and inhibiting the DNA gyrase enzyme. MIC value was obtained at the concentration of isolates Actinomycetes 10-2. MBC value cannot be determined. The antibacterial activity of isolates Actinomycetes is bacteriostatic. The results of the One Way ANOVA test showed p value = 0.000, which means that there is potentiality of Actinomycetes isolate as antimicrobials against Salmonella typhi.